Implementation of IoT Technology on MySmartTrash Waste Bank Application - Viva Arifin; Siti Ummi Masruroh; Rizka Amalia Putri; Fitri Mintarsih; Nenny Anggraini; Nurhayati; Dewi Khairani (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2025)
The effectiveness of Waste Bank in addressing national waste management challenges is limited by inherent shortcomings. Conventional processes, which heavily rely on manual labor and record-keeping, often face logistical challenges and inefficiencies that limit the effectiveness of waste banks. This paper presents the MySmartTrash application, a solution that integrates IoT technology to enhance waste management practices through a smart waste bank system. By utilizing IoT-enabled sensors, the application allows users to monitor waste levels in real time, thereby optimizing waste collection processes and promoting effective waste segregation. This study employed IoT Design Methodology and Prototyping. Through a SWOT analysis of existing waste management applications, the research identifies strengths and opportunities for enhancing waste management systems. Usability testing also highlighted the significance of various features. This study offers insights for future research into IoT applications in environmental sustainability and waste management systems.